The postcolonial politics of development - Kapoor, Ilan. (London ; New York : Routledge, 2008)
"This collection of essays is the first to chart what a specifically 'postcolonial politics' might look like in the context of global development so as to question development's dominant cultural representations and institutional practices." "The Postcolonial Politics of Development examines recent development policy initiatives in such areas as 'governance', 'human/gender rights', and 'participation' to better understand and contest how knowledge is produced in international development - its cultural assumptions and power implications. It shows how we, development practitioners and westernized elites/intellectuals, are complicit in this knowledge production. Such noble gestures as giving foreign aid or promoting participation and democracy often mask our institutional biases and economic and geopolitical interests, while silencing marginalized groups, on whose behalf we purportedly work."--BOOK JACKET.
Introduction Part 1: Postcolonial Insights?. -- 1. Capitalism, Culture, Agency: Dependency versus Postcolonial Theory.- 2. The Culture of Development Policy: Basic Needs, Structural Adjustment, Good Governance and Human Rights.- Part 2: Postcolonial Complicity and Self-Reflexivity?.- 3. Hyper-Self-Reflexive Development?: Spivak on Representing the Third World "Other"?.- 4. Participatory Development, Complicity and Desire.- 5. Foreign Aid as G(r)ift.- Part 3: Postcolonial Politics?.- 6. Deliberative Democracy or Agonistic Pluralism?: The Relevance of the Habermas-Mouffe Debate for Third World Politics.- 7. Acting in a Tight Spot: Homi Bhabha's Postcolonial Politics.- 8. Bend it like Bhabha: Hybridity and Political Strategy.- Conclusion.
Includes bibliographical references (p. 161-177) and index.
Keywords: Economic assistance; Economic development; Postcolonialism; Economic assistance -- Developing countries; Developing countries -- Economic conditions